Value Orientations of People Learning Toward Different Types of Culture: An Empirical Study - Rybak, Oksana Stepanivna (Journal of Education Culture and Society, 2018)
Aim. The aim of the research is to generalize the most topical scientific approaches to value orientations, disclose the importance of value orientations in personality development, and highlight the influence of culture on value orientation development. Methods. One hundred and eighty Ukrainian participants comleted the Milton’s Rokeach Test ‘Value Orientations’ (1973), Vladimir’s Sopov and Ludmila’s Karpushyna Morphology Test of Life Values (2001), Ludmila’s Pochebut Test ‘Cultural and Value Orientations’ (2004), Ivan’s Diachuk Test ‘Understanding of Moral Values’ (2010)Dmitrij’s Leontiev Test ‘Life Sense Orientations’ (2000). Answers to the tests made it possible to divide participants by different types of culture and built out hierarchy of values preferable for them. Results. The analysis shows that two clusters of examinees leaning toward different types of culture are empirically outlined. Their value orientations and dependence of the established values on the type of culture they lean toward is studied. The research has also indicated that in traditional culture and modern culture there is different hierarchy of values. Conclusions. Outlining of such types of culture as traditional, modern and dynamically developing culture enables clarification of special features of culture in general. Division of culture as the system into simpler subsystems, which are characterized by certain features, enables analysis of the very phenomenon of culture in detail. Besides that, in this study the importance of values and value orientations as an integral characteristic of culture is stressed.